Influence of Social Entrepreneurship Training on Job Creation in Ilorin's Small Business Sector - Jamiu, Tajudeen Ade; Adeoye, Moses Adeleke (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2023)
Small and medium enterprises, particularly micro-businesses have been the rescue platform for the survival and sustainability of the poor, unemployed youths and women as well as being the nursery-bed of entrepreneurship development in the nation. The study analyzes the influence of social entrepreneurship training on job creation in Ilorin's small business sector. The study focuses on understanding the impact of social entrepreneurship training programs on the ability of small business owners in Ilorin to create employment opportunities. The study adopted a descriptive survey research design. The study sampled 226 small business enterprises out of 520 using the Taro Yamane Coefficient of Variation formula. The researcher's instrument for data collection was a well-structured five-point Likert scale questionnaire which was administered to entrepreneurs from each selected entrepreneurial business type comprised of poultry farming, snail rearing, Rabbit rearing and 58 fish farming. The study adopted regression analysis and Pearson product moment correlation coefficient to test the hypotheses. The findings reveal that social entrepreneurship training has a significant positive influence on job creation in Ilorin's small business sector. Small business owners who have received training are more likely to create employment opportunities compared to those who have not undergone any training. It was concluded from the findings of the study that the social entrepreneurship development programs have greatly contributed to the rate of growth of small business enterprises in Ilorin.